Characterization of the complete chloroplast genome of an annual halophyte, Chenopodium glaucum (Amaranthaceae). Issue 2 (3rd July 2019) - Yao, Yan; Li, Xiao-Tong; Wu, Xi-Yue; Fan, Shou-Jin; Zhang, Xue-Jie; Qu, Xiao-Jian
Abstract: The complete chloroplast genome (plastome) of Chenopodium glaucum, an annual halophytic herb, was determined. The plastome was 152, 191 bp in size, containing a large single-copy region (83, 675 bp), a small single-copy region (18, 130 bp), and two inverted repeats regions (25, 193 bp). The overall GC content of this plastome was 37.2%. In total, 113 unique genes were annotated including 79 protein-coding genes (PCGs), 30 tRNAs and 4 rRNAs. Phylogenomic analysis showed that C. glaucum was sister to C. album .